Green Brand Products in Small and Medium Batik Industries with Pls-Sem Approach - Farida, Naili; Prihartini, Apriatni Endang; Ngatno, Ngatno (JURNAL ILMU SOSIAL, 2019)
This study examines Regiocentric Image Capabilities and Market Penetration on Green Products and the effect of Green Products on Marketing Performance. The sample in this study were 58 entrepreneurs of Small and Medium Batik Industries, who used natural colouring. The sampling technique used was purposive sampling, and the analysis technique used was PLS-SEM. The study found that Regiocentric Image Capabilities and Market Penetration significantly influence the Green Products, and it has a significant effect on Marketing Performance. Moreover, Green Brand Image does not influence a significant increase in Marketing Performance. These results indicated that Regiocentric Image Capabilities can enhance the capability of green product innovation with environmentally friendly natural colouring. The product is also supported by a broad market penetration capability. Furthermore, Green Brand Image on batik colouring products has no significant effect on marketing performance. The focus on green products appears so that the SMIs can increase marketing of environmentally friendly batik products.